2014
DOI: 10.1186/1756-0500-7-78
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus suppresses hemodialysis-induced increases in tear fluid secretion

Abstract: BackgroundHemodialysis is essential for the survival of patients suffering from chronic renal failure. However, in diabetics the incidence of dry eye disease is higher than in non-diabetic individuals. Accordingly, we evaluated if this difference is attributable to different effects of hemodialysis on basal tear fluid secretion.MethodsA modified Schirmer´s eye test determined if hemodialysis improved basal tear secretion rates in 36 diabetic and non-diabetic patients undergoing hemodialysis.ResultsBasal tear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Excessive levels of cytokines in DED inhibit the release of acetylcholine from the nerve endings and auto autoantibody blockade of M3AChR, disturbing the neuronal stimuli transmission to the secretory component of the OSM [ 117 , 118 ]. Moreover, diabetes can cause lachrymal and corneal neuropathy, and ultimately induce the change of OSM and dry eye [ 119 , 120 ]. Some ophthalmologic surgeries such as refractive surgery and cataract surgery could cause corneal nerve transection which results in decreased feedback to the lacrimal gland leading to reduced tear production [ 121 , 122 , 123 ].…”
Section: Ocular Surface Microenvironment Change In Dry Eyementioning
confidence: 99%
“…Excessive levels of cytokines in DED inhibit the release of acetylcholine from the nerve endings and auto autoantibody blockade of M3AChR, disturbing the neuronal stimuli transmission to the secretory component of the OSM [ 117 , 118 ]. Moreover, diabetes can cause lachrymal and corneal neuropathy, and ultimately induce the change of OSM and dry eye [ 119 , 120 ]. Some ophthalmologic surgeries such as refractive surgery and cataract surgery could cause corneal nerve transection which results in decreased feedback to the lacrimal gland leading to reduced tear production [ 121 , 122 , 123 ].…”
Section: Ocular Surface Microenvironment Change In Dry Eyementioning
confidence: 99%
“…Hyperglycaemia-induced AGE and sorbitol accumulation within the cells leads to cellular oedema and dysfunction, resulting in structural and functional damage of the lacrimal gland [69]. Additionally, diabetic neuropathy impairs the autonomic control of the lacrimal gland [70]. Consequently, both these factors decrease the capacity of the lacrimal gland to produce tears.…”
Section: Tear Film Functionmentioning
confidence: 99%
“…Diabetic neuropathy may be an important risk factor for lacrimal gland dysfunction. Nakata et al demonstrated that diabetes suppresses hemodialysis-induced increases in tear fluid secretion, which suggests that autonomic control of lacrimal gland function may be compromised by neuropathy in patients with DM [ 19 ].…”
Section: Etiology Of Diabetes Mellitus Associated Dry Eye Syndromementioning
confidence: 99%